This preview shows page 1. Sign up to view the full content.
Unformatted text preview: y = 1
æ 7 öæ 1 ö
y = -ç ÷ç ÷
è 3 ø è 14 ø
y=6 14 y = 1 - © 2007 Paul Dawkins 318 http://tutorial.math.lamar.edu/terms.aspx College Algebra Finally, substitute this into the original substitution to find x. 121
æ 1ö 2
x = 2ç - ÷ + = - + =
è 6ø 3
So, the solution to this system is x = 1
and y = - .
[Return to Problems] As with single equations we could always go back and check this solution by plugging it into
both equations and making sure that it does satisfy both equations. Note as well that we really
would need to plug into both equations. It is quite possible that a mistake could result in a pair of
numbers that would satisfy one of the equations but not the other one.
Let’s now move into the next method for solving systems of equations. As we saw in the last part
of the previous example the method of substitution will often force us to deal with fractions,
which adds to the likelihood of mistakes. This second method will not have this problem. Well,
View Full Document
- Spring '12